The role of physical activity in type 1 diabetes: a review of the literature - Monika Gaszyńska; Antonina Drzewiecka; Artur Drzewiecki; Wiktor Korczak; Maria Anna Madejska; Aleksandra Rudzka; Wojciech Falkowski; Anna Krysińska; Weronika Woźniak; Jakub Magielski (Journal of Education, Health and Sport)
Introduction and Purpose: Diabetes is a prevalent metabolic disorder affecting over 530 million people globally, with its incidence increasing alarmingly. Due to the early onset of type 1 diabetes (T1D), treatment and prevention of complications are critical. This study aims to present the safety profile of physical activity, its effects on metabolic processes, and the benefits of exercise in preventing late complications of T1D.